BmHSP20.8 is Localized in the Mitochondria and has a Molecular Chaperone Function In Vitro. Issue 1 (14th July 2015) - Wu, Chengcheng; Wang, Chan; Li, Dan; Liu, Yue; Sheng, Qing; Lv, Zhengbing; Yu, Wei; Nie, Zuoming
Abstract : Heat shock proteins (HSPs) are abundant and ubiquitous in almost all organisms from bacteria to mammals. BmHSP20.8 is a small (sHSP) in Bombyx mori that contains a 561 bp open reading frame that encodes a protein of 186 amino acid residues with a predicted molecular mass of 20.8 kDa. The subcellular localization prediction indicated that BmHSP20.8 is likely distributed in the mitochondria with a 51% probability. To identify the subcellular localization of BmHSP20.8, three recombinant vectors were constructed and used to transfect BmN cells. The cytoplasmic and mitochondrial proteins were extracted 72 h after transfection. The Western blot showed that recombinant BmHSP20.8 exists only in the mitochondria. To locate the mitochondrial localization signal domain of BmHSP20.8 more accurately, we cloned four truncated recombinant vectors. The Western blot analysis of the cytoplasmic and mitochondrial proteins showed that the mitochondrial localization signal domain of BmHSP20.8 is located between amino acids 143 to 186. We constructed the pETduet-HIS-SUMO-BmHSP20.8 vector and a soluble BmHSP20.8 was expressed. In a citrate synthase (CS) thermal aggregation experiment, we found that the recombinant BmHSP20.8 protein can protect CS from aggregating at 43 and 48°C and thus exhibited molecular chaperone activity. Taken together, the results showed that BmHSP20.8 could be a mitochondrial protein and has a molecular chaperone activity, suggesting an important role in mitochondria.